The Relationship between Mathematical Literacy and Students’ Problem-Solving Ability: A Study in Indonesian Secondary Education - Norma Nasir; Syamsinar; Fadhilah Nur Sa'diyyah (Research Collaboration Community (Rescollacom), 2026)
This study aims to examine the relationship between mathematical literacy and students’ problem-solving ability in mathematics learning. Mathematical literacy is considered a fundamental competency that enables students to interpret, formulate, and apply mathematical concepts in various real-life contexts, while problem-solving ability reflects students’ capacity to understand, plan, execute, and evaluate solutions to mathematical problems. This research employed a quantitative approach with a correlational design. The study was conducted at MA Arifah Gowa, involving 60 secondary school students selected through purposive sampling. Data were collected using two instruments: a mathematical literacy test and a problem-solving ability test. The collected data were analyzed using descriptive statistics and Pearson Product-Moment correlation. The results show that students’ mathematical literacy has a mean score of 65.25 (SD = 10.12), indicating a moderate level, while problem-solving ability has a mean score of 82.40 (SD = 6.85), indicating a relatively high level. The correlation analysis reveals a significant positive relationship between mathematical literacy and problem-solving ability (r = 0.68, p < 0.05). These findings indicate that students with higher mathematical literacy tend to demonstrate better performance in solving mathematical problems. Mathematical literacy plays a crucial role in supporting students’ ability to understand problem contexts, select appropriate strategies, and interpret solutions effectively. However, the moderate level of literacy suggests that students may still rely on procedural approaches rather than deep conceptual understanding. In conclusion, enhancing mathematical literacy is essential for improving students’ problem-solving ability. Therefore, mathematics instruction should emphasize contextual understanding, reasoning, and application to foster more meaningful learning outcomes.